pH Degrees and Reductation Scores of Pasteurization Cow’s Milk in Different Time of Storaging - Umar U; Razali R; Andi Novita (Universitas Syiah Kuala, 2014)
The aimed of this study was to determine the effect of storage time of pasteurized cow's milk in a the certain period of time on pH value and reductase score. A total of 4 liters of cow's milk as a cage samples purchased from UD. Atjeh Live stock Farm Lamnyong Darussalam wasexamined for pH value and reductase score after pasteurized and stored for 28 days at refrigerator temperature (2-4C). The design used in thisstudy was completely randomized design with five treatments and four replications. Group I was control group, group II, III, IV, and V werestored for 7, 14, 21, and 28 days, respectively. The results showed that pasteurized milk stored for 28 days showed a different pH values, but thedifference in pH within SNI standard (P 0.05). Based on the reductase score, milk is able to keep for only 2 weeks, while in third and fourthweek, the reductase score is not accepted by SNI standard with the value of 1.____________________________________________________________________________________________________________________Key words: reductation score, pH degrees, pasteurization, milk